Community perceptions on climate change effect and household food security in Karatu District, Tanzania - Kyusilu, Jacqueline (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the award of the Degree of Master of Science in Environmental Management (MSc EM) of Mzumbe University